(untitled) (American Journal of Aquaculture and Animal Science, 2025)
The nutritional value of feeding Labeo rohita fingerlings with different levels of Prunus amygdalus seed meal was evaluated for 56 days. Five isoproteic diets containing 40% crude protein were formulated by incorporating different levels of Prunus amygdalus seed meal (0.0, 0.5, 1.0, 1.5, and 2.0g/100g), and designated as PA1- PA5 respectively. A total of 225 Labeo rohita fingerlings with a mean weight of 5.76±0.10g were randomly allocated into 15 glass tanks (measuring 70 × 45 × 45 cm), each filled with 70 liters of water. Fish were stocked at a rate of 15 per tank, corresponding to five dietary treatments with three replicates each. The results revealed that significant differences (P˂0.05) were observed in all the growth performances. Fish on PA4 had the best growth performance compared to other treatments and control. Fish fed PA4 had the highest survival (%) while PA1 (control) had the lowest survival (%). All water quality parameters (DO, temperature, and pH) remained within optimal and acceptable ranges for the fish during the experimental period. There were significant variations (P < 0.05) in the haematological profile of the experimental fish. Notably, the 1.5g inclusion level (PA4) yielded a well-balanced biochemical response, marked by increased protein and globulin, stable glucose levels, and reduced cholesterol, which indicates optimal metabolic and immune conditions at this concentration.